ANALISIS OPTIMALISASI PENGGUNAAN INPUT USAHATANI TEMBAKAU DI DESA ALASSUMUR LOR KECAMATAN BESUK KABUPATEN PROBOLINGGO - Achmad Munir; Sri Hindarti; Moch. Noerhadi Sudjoni (Program Studi Agribisnis, 2019)
ABSTRACKThe objective of doing this research is 1.) To find out the efficiency of tobacco business in Alssumur Lor Village, Besuk District, Probolinggo Regency 2.) To find out the factors that influence the production of tobacco farming in Alassumur Lor Village Probolinggo district, to analyze the optimization of the use of the factors of production of tobacco usahatani in Alassumur Lor Village, Besuk District tobacco farming was efficient, because this is showed by the R/C ratio of 3.22 for usahatani tobacco. So that the farming is feasible to be applied. The tobacco farming system is advantageous because the R/C value of the retiois greater than 1. From the results testing of the F using regression analysis are obtained F value of 78.61 with the probability is obtained is 0.1 or more than 00.5 at a confidence level 0f 78% then it can beinterpreted simultaneously, variables in the model significantly influence tobacco production. And from the results of the optimization analysis of the use of tobacco farming production input shows the estimation of the use of seeds by 49.71 with more than 1 results so than it is not optimal, then it is necessary to add seedlings to 948.71 seeds/ha. Estimation of the use of Za fertilizer is 1.30 with more than 1 results so that it is not optimal, it is necessary to add Za fertilizer to 371.79 kg per hectare. Estimation of the use of phonska fertilizer is 1.03 with more than 1 results so that it is not optimal, it is necessary to add the estimaton of phonska fertilizer to 47.84 kg per hectare Keywords: Tobacco farming optimization of tobacco input